The accuracy and reliability of the Suchey–Brooks pubic symphysis age estimation method: Systematic review and meta‐analysis. Issue 1 (7th October 2021) - Schanandore, James V.; Wolden, Mitch; Smart, Neil
Abstract: Suchey–Brooks method has been studied many times with varying reports of accuracy and reliability. A systematic review and meta‐analyses were utilized to quantitatively determine the accuracy and reliability of the Suchey–Brooks (S‐B) method. A systematic search of PubMed and EBSCO health and medical databases was performed. Meta‐analyses were performed to quantify the relationship between actual known age at death and the S‐B method using Spearman's Rho and Pearson's r for (1) combined males and females estimates, (2) male‐only estimates, and (3) female‐only estimates. Overall correlation coefficient using Cohen's kappa, Spearman's Rho, and Pearson's r was also calculated to determine the interrater and intrarater reliability using the S‐B method. Eighteen studies classified as moderate‐to‐high methodological quality met the inclusion criteria. The sample sizes were different for the combined male and female ( n = 2620), male‐only ( n = 2602), and female‐only ( n = 1431) meta‐analyses. The effect size of the age at death meta‐analyses was large and significant for combined males and females (Spearman's Rho = 0.62; Pearson's r = 0.65), male‐only (Spearman's Rho = 0.77; Pearson's r = 0.75), and female‐only (Spearman's Rho = 0.71; Pearson's r = 0.71). The overall correlation coefficients of the interrater (Kappa = 0.76; Spearman's Rho = 0.73; Pearson's r = 0.80) and intrarater (Kappa = 0.81; Spearman's Rho = 0.91; Pearson's r = 0.83) reliability meta‐analyses were large and significant. A significant degree of heterogeneity was present in all meta‐analyses, with minimal evidence of publication bias. The meta‐analyses results suggest the S‐B method is highly reliable with a moderate‐to‐high degree of accuracy. Our results also identified sample size and accuracy differences between male and female individuals.